Callus culture for biomass production of milk thistle as a potential source of milk clotting peptidases - Cimino, Cecilia Verónica (2006)
The objective of this work was the optimization of the conditions of in vitro culture for callus production of Silybum marianum (L.) Gaertn. (Asteraceae). Sections of cotyledons, previously disinfected by washing successively with ethanol 70º, NaClO (10% w/v) and Tween 20 (0.05% v/v) and rinsing with sterile distilled water, were used as explants. For its initial culture, B5 medium supplemented with BA and 2,4-D solidified with phytagel was used, and a 63% survival was achieved. To obtain callus, two solid media were assayed (S1 and S2) using B5 medium supplemented with growth regulators (BA and 2,4-D or NAA and BA, respectively). The calli were grown at 25ºC during 45 days in darkness. Growth kinetics was studied using S1 medium obtaining a typical growth curve with an exponential phase after 14 days of incubation (rate of growth 0.005 g dry weight/ day) and stationary phase after 35 days. The rate of growth in S2 medium was slower, and rhizogenesis was observed starting on the fifth week of incubation. From these results, the best culture medium for callus production of Silybum marianum was S1 medium.